On the Behavior of the Solution of the Wave Equation - Hendra Gunawan; Wono Setya Budhi (Institut Teknologi Bandung, 2004)
We shall here study some properties of the Laplace operator through its imaginary powers, and apply the results to understand the behavior of the solution of the wave equation.